Coward A Clough Yn Y Collodi Cymraeg. (Architects' Journal, 2021)
The Third Man is the creation of CZWG associate Patrick Massey, constructing imagined conversations between historical figures from their own words, facilitated by the anonymous "Third Man" Portmeirion, Merionethshire, north Wales Designer and curator: Clough Williams-Ellis, 1925-1973 Guest: Noël Coward, staying in the Fountain 2 (Upper Fountain) suite[sup 2] EXT. Clough Williams-Ellis, Noël Coward and the Third Man step out from beneath the colonnade. The Pantheon, or Dome, was built 1960-61 to remedy what CWE described as Portmeirion's "dome deficiency".